2008
DOI: 10.2166/wh.2008.060
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Cryptosporidium parvum among children after a school excursion to an adventure farm, South West England

Abstract: We present the results of an outbreak investigation on a Cryptosporidium parvum outbreak among 35 people, (27 students and 8 teachers), who participated in a school excursion to an outdoor adventure farm in South West England, from 22 to 26 May 2006. A cohort study was implemented to investigate possible sources of infection during the farm visit. The most likely transmission route was contact with faecally contaminated surface water following heavy rainfall, or consumption of water from the private well. Disi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…For cryptosporidiosis, proximity to an E. coli-impaired stream (STREAM) was associated with increased risk for disease, which is in agreement with risk factors reported in other studies [38][39][40]. Contact with contaminated water may be more likely the closer the patient resides to the stream, although it is important to note that proximity to a stream does not necessarily mean that contact occurs between an individual and the contaminant, and no data were available to determine whether individuals with either disease had physical contact with recreational water.…”
Section: Surface Water Qualitysupporting
confidence: 89%
“…For cryptosporidiosis, proximity to an E. coli-impaired stream (STREAM) was associated with increased risk for disease, which is in agreement with risk factors reported in other studies [38][39][40]. Contact with contaminated water may be more likely the closer the patient resides to the stream, although it is important to note that proximity to a stream does not necessarily mean that contact occurs between an individual and the contaminant, and no data were available to determine whether individuals with either disease had physical contact with recreational water.…”
Section: Surface Water Qualitysupporting
confidence: 89%
“… Sheep, goats, “farm animals” a Urine/milk–oral/respiratory Droplet, contact, aerosol 2 [55] , [85] Campylobacter spp. Cattle, dairy cattle, chickens, pigs Faecal–oral Droplet, contact, aerosol 2 [102] , [111] Chlamydophila psittacosi Poultry, chickens, turkeys Respiratory Airborne, aerosol 2 [24] , [101] Coxiella burnetii Goats, sheep, cattle, poultry, “farm animals” a Faecal–respiratory Airborne, aerosol, dust 11 [25] , [26] , [28] , [40] , [41] , [48] , [54] , [55] , [99] , [100] , [120] Cryptosporidium parvum Cattle, sheep, buffalo Faecal–oral Droplet, contact, aerosol 3 [18] , [81] , [93] Extended-Spectrum-β-lactamase producing Enterobacteriaceae Poultry Faecal–respiratory/oral Dust, aerosol, airborne 1 [98] Hepatitis E virus …”
Section: Resultsmentioning
confidence: 99%
“…Survey laboratory practices in the UK have recently included screening of all fecal specimens from children aged 15 or younger, with routine reports to the Communicable Disease Surveillance Centre (CDSC) of the PHLS ( Public Health Laboratory Service ) (Table 3) [245]. Among the described outbreaks (see Sections 3.1 and 3.2), in many episodes the children represented the largest portion of confirmed cases of cryptosporidiosis [84, 246–251] (Table 4). The work by Chalmers et al, 2009 [63] showed that the epidemiology of human cryptosporidiosis in UK, from 2000 to 2003, importantly differed among Cryptosporidium infecting species with reference to children age groups (Table 1) (Figure 3).…”
Section: Cryptosporidiosis In Childrenmentioning
confidence: 99%